2012
DOI: 10.1111/j.1600-6143.2011.03948.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Lentivirus-Mediated Overexpression of Programmed Death-Ligand 1 on Corneal Allograft Survival

Abstract: To investigate the role of lentivirus-mediated overexpression of programmed death-ligand 1 (PD-L1) on rat corneal allograft survival. A fully allogeneic rat cornea transplant model was used for in vivo studies. Lentiviral (LV) vectors are efficient tools for ex vivo genetic modification of cultured corneas. LV vector encoding for PD-L1 (LV.PD-L1) and LV vector encoding for eGFP (LV.eGFP, as control) were constructed and tested. PD-L1 or eGFP expression was increased on corneal cells upon LV.PD-L1 and LV.eGFP t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…For example, a fusion protein CTLA4-Ig (Abatacept) has been used in the clinic for treating autoimmune diseases such as rheumatoid arthritis 48 . Similarly, local overexpression of PD-L1-Ig or administration of purified PD-L1-Ig has been shown to promote allograft survival in murine models 4952 . Our study indicates that enhancing the anti-inflammatory function of VISTA may benefit the treatment of a variety of inflammatory and autoimmune disorders.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a fusion protein CTLA4-Ig (Abatacept) has been used in the clinic for treating autoimmune diseases such as rheumatoid arthritis 48 . Similarly, local overexpression of PD-L1-Ig or administration of purified PD-L1-Ig has been shown to promote allograft survival in murine models 4952 . Our study indicates that enhancing the anti-inflammatory function of VISTA may benefit the treatment of a variety of inflammatory and autoimmune disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Previous results from our group have shown that both lentivirus-mediated overexpression of programmed deathligand 1 on corneal cells (23) and intravenous administration of donor-derived BM-derived dendritic cells (42) can significantly inhibit NKT cell infiltration into the corneal allograft. Although in this study we used a different approach (systemic infusion of MSCs), this finding was replicated in the case of both allo-and third-party MSC treated recipients, perhaps confirming the importance of this cell type in determining the fate of the allograft.…”
Section: Discussionmentioning
confidence: 88%
“…Orthotopic corneal transplantations were performed and evaluated as reported previously (23). Briefly, graft transparency, as the primary indicator of rejection, was evaluated every second day and graded as follows: 0-completely transparent cornea; 0.5-slight corneal opacity, iris structure easily visible; 1.0-low opacity with visible iris details; 1.5-modest corneal opacity, iris vessels still visible; 2.0-moderate opacity, only some iris details visible; 2.5-high corneal opacity, only pupil margin visible; 3.0-complete corneal opacity, anterior chamber not visible.…”
Section: Animals and Corneal Transplantationmentioning
confidence: 99%
“…Furthermore, systemic application of a soluble PD-L1-Ig fusion protein was able to prolong allogeneic graft survival in a mouse corneal transplant model [39] highlighting the importance of this pathway. We showed that LV-mediated overexpression of PD-L1 in cultured corneas significantly prevents corneal graft rejection by modulating graft-infiltrating cells [40]. This striking result was associated with a reduction of natural killer T cells and cytotoxic CD8+ T cell infiltration, and was also accompanied by attenuation of pro-inflammatory cytokine expression [40].…”
Section: Gene-therapeutic Applications To Prevent Corneal Allograft Rmentioning
confidence: 99%
“…We showed that LV-mediated overexpression of PD-L1 in cultured corneas significantly prevents corneal graft rejection by modulating graft-infiltrating cells [40]. This striking result was associated with a reduction of natural killer T cells and cytotoxic CD8+ T cell infiltration, and was also accompanied by attenuation of pro-inflammatory cytokine expression [40]. Interestingly, the neovascularisation of transplanted corneas seemed to be unaffected by this therapy.…”
Section: Gene-therapeutic Applications To Prevent Corneal Allograft Rmentioning
confidence: 99%